Charcoal hemoperfusion vs. high efficiency hemodialysis in carbamazepine intoxication: A case report [Karbamazepin i̇ntoksikasyonunda karbon hemoperfüzyon mu yüksek etkinlikli hemodiyaliz uygulamasi mi?: Bir olgu sunumu] - AŞICIOĞLU, EBRU; KOÇ, MEHMET (My University, 2011)
Carbamazapine is a commonly used antiepileptic agent. Neurological abnormalities which can progress to coma, arrhythmias, respiratory depression and eye abnormalities such as nystagmus are seen in an intoxication setting. There is no specific antidote for the treatment of carbamazepine intoxication and supportive therapy is generally recommended. Carbamazepine is not removed through conventional hemodialysis as it highly bound to proteins. Charcoal hemoperfusion has been reported as the standard effective treatment method. Herein we report a 23-year-old woman with high dose carbamazepine overdose treated with high efficiency hemodialysis and charcoal hemoperfusion. We also discuss a comparison of the methods used for carbamazepine intoxication.
Keywords: Carbamazepine; Hemodialysis; Hemoperfusion; Intoxication